Economic Efficiency Assessment of Biopreparation Production Based on Epiphytic Bacteria on an Industrial Scale - Djuraevna, Ruzieva, Inobat; Hasanovich, Mammadiev Abdusahat (American Journal of Biology and Natural Sciences, 2025)
In this article, the following varieties of gossypium hirsutum L. were selected from farms near industrialized areas of Shorchi district: C6524, An-Boyovut-2, Andijan 37, Bukhara 6, C4727, Zharkurgan. These test varieties were grown in liquid nutrient medium with the associatively viable bacteria Bacillus subtilis SKB-256 to obtain a biopreparation based on epiphytic bacteria on an industrial scale. Biohumus, phosphogypsum, manure, soil and wood chips were used as environmentally friendly substrates, and their agrophysical, physicochemical and biological properties, which determine the level of soil productivity in order to obtain high-quality crops from plants, were also studied.